2020
DOI: 10.1017/s0007114520003724
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of branched-chain amino acids and colorectal cancer risk

Abstract: ABSTACT An adequate intake of branched-chain amino acids (BCAAs) is required for protein synthesis and metabolic functions, including insulin metabolism. Emerging studies found positive associations between BCAAs and the risk of various diseases sharing etiological aspects with colorectal cancer (CRC), including type 2 diabetes, obesity, and pancreatic cancer. We investigated the relation between dietary BCAAs and CRC using data from a multicentric Italian case-control study, including 1953 cases of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Third, an ex vivo/in vitro report [69] demonstrated that isoleucine, in a mouse liver metastatic colon cancer model, partly exerted antiangiogenic effects via the mTOR pathway by inhibiting (VEGF) synthesis. In line with these observations, two recent epidemiological reports from Italy [70] and the United States [71] found a modest inverse relationship between dietary BCAA intake and CRC. In another study, branched-chain α-keto acid dehydrogenase (BCKDH) expression has been linked to CRC tumorigenesis via the mitogen-activated protein kinase (MAPK) pathway ex vivo [72].…”
Section: The Pathophysiology Of Bcaa Metabolism In Multiple Cancerssupporting
confidence: 68%
“…Third, an ex vivo/in vitro report [69] demonstrated that isoleucine, in a mouse liver metastatic colon cancer model, partly exerted antiangiogenic effects via the mTOR pathway by inhibiting (VEGF) synthesis. In line with these observations, two recent epidemiological reports from Italy [70] and the United States [71] found a modest inverse relationship between dietary BCAA intake and CRC. In another study, branched-chain α-keto acid dehydrogenase (BCKDH) expression has been linked to CRC tumorigenesis via the mitogen-activated protein kinase (MAPK) pathway ex vivo [72].…”
Section: The Pathophysiology Of Bcaa Metabolism In Multiple Cancerssupporting
confidence: 68%
“…Although this result should be interpreted with caution given the reduced number of cases, various etiological factors and biological aspects are different according to CRC sites. Physical activity, antibiotic use and family history of CRC are relevant in colon but not in rectal cancer [ 37 , 38 , 39 , 40 ], and associations of some dietary components are stronger for some colon subsites cancers [ 41 , 42 ]. Moreover, the proximal and distal colon have a different embryological origin, also resulting in a distinct vascular supply [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, various factors and biological aspects were different according to CRC sites. Physical activity, antibiotic use and family history of CRC were relevant in colon but not in rectal cancer [52,53,54,55], and associations of some dietary components were found to be stronger for the cancer of some colon subsites [56,57]. Moreover, the proximal and distal colon have a different embryological origin, also resulting in a distinct vascular supply [58].…”
Section: Discussionmentioning
confidence: 99%